Analisis Tingkat Kepuasan Nasabah terhadap Dimensi Kualitas Layanan pada BPR BDE Pakem Sleman dengan Pendekatan Importance-Performance Analysis - Andriya Risdwiyanto (Jurnal Maksipreneur, 2014)
The survey was conducted in the research process to determine the level of customer satisfaction on service quality dimensions of Rural Bank Bakti Daya Ekonomi (BPR BDE) Pakem Sleman, Yogyakarta and to determine the dimensional attributes of services which one is considered the most important by the customer in the decisionmaking of services using in BPR BDE Pakem Sleman, Yogyakarta. This research is based on five variables, namely SERVQUAL i.e. Reliability (ability of the company to provide prompt service and reliable), Responsiveness (responseability or alertness companies to help customers and provide fast service), Assurance (ability, courtesy, and trustworthiness which is owned by the staff, danger free, risk, and doubt), Empathy (the ease of having good communications and able to understand customer needs), and Tangible (physical facilities, equipments, employee performance, and means of communications). The analysis is performed based on an approach of importance performance analysis that show the dimensions of empathy and assurance are considered the most influence on the customers decision to use the services of BPR BDE Pakem Sleman, Yogyakarta.